Lurasidone for Adolescents With Complex Mental Disorders: A Case Series. (October 2022) - Mole, Tom B.; Furlong, Yulia; Clarke, Richard J.; Rao, Pradeep; Moore, Julia K.; Pace, Giulia; Van Odyck, Hugo; Chen, Wai
Objectives: Lurasidone is a new second generation (atypical) antipsychotic agent with unique receptor affinity and side-effect profiles, but limited literature is available on its use in adolescent populations. Contrasting with research treatment trials which typically recruit patients by stringent selection criteria, this case series examined the effects and tolerability of using lurasidone in adolescents within real-life clinical settings in treating complex cases who had not responded to other therapy options. Methods: We conducted a retrospective case-note audit of 6 adolescents aged 14 to 17 years old attending community child and adolescent mental health services (CAMHS) who were prescribed lurasidone. Results: Lurasidone had been prescribed for a range of "hard-to-manage" conditions with complex comorbidities, in adolescents in relation to specific use of lurasidone on the basis of clinical and pharmacological indications after exhausting more conventional treatment options. Case-note review suggested response to lurasidone was clinically positive in 3 cases, equivocal/marginal in 2 cases, and ineffective in 1 case. There were no cases of poor tolerance or adverse effects. Notably, positive responses for depressive and irritable mood symptoms were specifically recorded by prescribing clinicians, indicative of benefits on symptom improvement. No lurasidone attributed weight gain, galactorrhoea, metabolic abnormalities, sexual dysfunction or intolerance were reported. Pro-cognitive effects were not detected; but our findings were constrained by the non-systematic and incomplete information ascertainment, typical in retrospective case-note review. Conclusion: This case series provides preliminary data supporting lurasidone's potential use in adolescents of complex clinical needs (but without a clinical diagnosis of bipolar disorder) within real-life clinical settings. Lurasidone appears to show a weight-sparing effect, in addition to improving mood symptoms in some cases. Lurasidone deserves further study for its use in the adolescent population (outside the remit of FDA) given its potential more favorable risk-benefit profile in young people. The favorable tolerability appear to be borne out by the pharmacodynamic predictions in our complex patients who would be excluded in formal clinical trial studies.